Fire tablets for dummies - Muir, Nancy (John Wiley & Sons, 2015)
Amazon's growing suite of tablets gives you the power to watch, work, and play wherever you roam. With access to a large music and video collection, a growing app store, a massive library of e-books, and fast, easy one-click shopping, the Fire Tablet is the hottest ticket in town. Whether you're the owner of the original Kindle Fire, Kindle Fire HD, Kindle Fire HDX, or one of the latest and greatest Fire tablet models, this fun and friendly guide will fuel your love of your tablet and help you make the most of its myriad features and capabilities.